PERAN GURU DALAM IMPLEMENTASI PEMBELAJARAN BERBASIS TRI PUSAT PENDIDIKAN DI SDN 01 KLEGEN - Anita Ema Ridiyawati; Mundrikah; Soedjono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the role of teachers in implementing Tri-Center Education-based learning (family, school, and community) at the elementary school level. The research uses a descriptive qualitative approach, involving interviews and observations with teachers, parents, and community members. The results show that teachers play a crucial role as a bridge between the school, family, and community in supporting students' learning processes. Teachers not only deliver lesson content but also design learning that is relevant to students' lives, utilizing values derived from family and community. Furthermore, effective communication between teachers, parents, and the community is key to supporting the holistic development of students. Overall, this study emphasizes the importance of the teacher's role in creating an inclusive learning environment that supports the overall growth of students.